STUDENTS' CRITICAL THINKING SKILL AND ENVIRONMENTAL AWARENESS IN LEARNING ENVIRONMENTAL POLLUTION USING INSTAGRAM-MEDIATED SAMR MODEL - Handina, - (2019)
Environmental awareness is essential for students understanding of the environment's current situation and the importance of its protection. However, limited class time and huge class size issues have limited student involvement and thinking attempts. Consequently, the results of class discussion tend to end up being superficial, having little impact on student environmental awareness and critical thinking. This study aims to analyze students' critical thinking skills and environmental awareness in learning environmental pollution through the Instagram-mediated SAMR model. At the end of the research, student learning satisfaction was also measured. The students involved in this research were instructed to follow an Instagram account in which they learned the topic, interacted with each other and the teacher, and submitted their vlog projects. Students' critical thinking skill data was collected using a rubric, while students' environmental awareness and learning satisfaction data were collected using online questionnaires. The data were analyzed descriptively. Students' critical thinking skill average score is categorized as satisfactory, their environmental awareness shows that the students do care about environmental issues, and their learning satisfaction rating percentage is 77% which means the students are very satisfied with the learning activity. Keywords: Students Critical Thinking Skill, Students Environmental Awareness, Environmental Pollution, SAMR Model, Instagram